1982
DOI: 10.1111/j.1398-9995.1982.tb02318.x
|View full text |Cite
|
Sign up to set email alerts
|

Total Serum IgE Concentrations in Adolescents and Adults Using the Phadebas IgE PRIST® Technique

Abstract: Total serum IgE measured with the Phadebas PRIST technique was titrated in 117 normal non-allergic subjects, 237 allergic adolescents or adults and 89 non-allergic patients who suffered from asthma, rhinitis, or conjunctivitis. All subjects were of Caucasian origin. In normal subjects, mean total serum IgE was 38 +/- 43 kU/l. This value is exactly the same as that found in a study of Caucasian New Zealanders and very similar to the values found in most U.S. studies. This suggests that the mean total serum IgE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1
2

Year Published

1984
1984
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 16 publications
2
23
1
2
Order By: Relevance
“…This finding confirms observations made in Tucson, USA [5] and in Greece [19], whereas it is in contrast with other studies [4,20,26]. Recently, JARVIS et al [8] have found, in a stratified random sample of 20-44 yr old subjects living in East Anglia, that, among nonsmokers, geometric mean total IgE was higher in males than females.…”
Section: Discussioncontrasting
confidence: 56%
“…This finding confirms observations made in Tucson, USA [5] and in Greece [19], whereas it is in contrast with other studies [4,20,26]. Recently, JARVIS et al [8] have found, in a stratified random sample of 20-44 yr old subjects living in East Anglia, that, among nonsmokers, geometric mean total IgE was higher in males than females.…”
Section: Discussioncontrasting
confidence: 56%
“…Interestingly, atopic patients with vit iligo showed a tendency to normal IgE levels, as 55.6% had IgE values in the normal range. Most of the recent studies using the PRIST technique with a cutoff level of 100 kU/1 showed normal IgE values in about 20% of atopic subjects (table I) [21,29,32]. Our results correlated with those of Przybilla et al [34].…”
Section: Discussionsupporting
confidence: 82%
“…Based on the moderate sensitivity of the ELISA, it is quite possible that the percentage of donors containing biologically relevant concentrations of CCL23 is much higher than 26%. Serum IgE levels higher than 100 kU/L serve as one of several parameters indicative of atopy in adults (37). Thus, the same plasma samples were analyzed for IgE concentrations (Table I).…”
Section: Resultsmentioning
confidence: 99%